2018
DOI: 10.1177/1087054718802014
|View full text |Cite
|
Sign up to set email alerts
|

Media Use, Sleep Quality, and ADHD Symptoms in a Community Sample and a Sample of ADHD Patients Aged 8 to 18 Years

Abstract: Objective: Relationships between sleep, screen-based media, and ADHD symptomatology were investigated using a case- and community-based approach. Method: N = 357 healthy and N = 61 children with ADHD (12.72 ± 2.83 years) completed a sleep and media questionnaire. To measure ADHD symptomatology, parents filled out the Strengths and Weaknesses of ADHD symptoms and Normal behavior (SWAN) scale. Two samples were formed: a matched ( N = 61 patients and N = 61 controls) and a community sample ( N = 357 healthy parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 91 publications
(109 reference statements)
1
24
0
1
Order By: Relevance
“…Indeed, although the literature shows the association between sleep duration and ADHD, most of the previous studies presented no adjusted analyses or utilized an insufficient/inadequate control method (Scott et al, 2013; Williams & Sciberras, 2016). Although we cannot rule out the potential role of unfavorable sleep–wake behavior or variability in sleep schedules, which have already been reported in ADHD (Craig et al, 2017; Scott et al, 2013; Thoma et al, 2018), for the few associations observed for shorter nocturnal and greater daytime sleep duration at 48 months, confounding seems to be an important issue in the current literature. Future studies should more thoroughly explore this issue to report adequate estimates.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, although the literature shows the association between sleep duration and ADHD, most of the previous studies presented no adjusted analyses or utilized an insufficient/inadequate control method (Scott et al, 2013; Williams & Sciberras, 2016). Although we cannot rule out the potential role of unfavorable sleep–wake behavior or variability in sleep schedules, which have already been reported in ADHD (Craig et al, 2017; Scott et al, 2013; Thoma et al, 2018), for the few associations observed for shorter nocturnal and greater daytime sleep duration at 48 months, confounding seems to be an important issue in the current literature. Future studies should more thoroughly explore this issue to report adequate estimates.…”
Section: Discussionmentioning
confidence: 69%
“…Exposure to blue light from these devices has been associated with a greater alteration of circadian rhythms, as well as a higher prevalence of sleep-onset insomnia and poorer sleep quality ( 64 ). Some authors point out an excessive use of technology at night in the ADHD population ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in routine, structure, and social contact associated with COVID-19 restrictions, as well as increasing uncertainty, may exacerbate ADHD symptoms and associated problems ( Cortina et al, 2020 ). Furthermore, more time inside and fewer opportunities for exercise may contribute to a worsening of sleep problems ( Becker & Gregory, 2020 ) and increased media use in children with ADHD; aspects of life that are that are commonly challenging for families of children with ADHD to regulate ( Cortese et al, 2013 ; Thoma et al, 2020 ). Positives may also be experienced as a result of the COVID-19 restrictions.…”
mentioning
confidence: 99%